Análise prosódica da fala de sujeitos com dificuldades escolares pré e pós terapia auditiva acusticamente controlada - Pereira, Adriana Bonachela Rodrigues (2021)
INTRODUCTION: School-age children may have Auditory Processing Disorder (APD), which, in turn, can interfere with the development of speech and learning, generating academic and social difficulties. OBJECTIVE: To compare, from the perceptual and acoustic points of view, the speech of subjects with school difficulties and diagnosis of APD, pre and post Acoustically Controlled Hearing Therapy (ACHT). METHODS: A multiple case study was carried out with 04 subjects equally distributed according to sex, aged between 8 years and 11 months to 17 years and 11 months at the beginning of the research. The subjects were submitted to procedures of: basic audiometric evaluation (audiometry, imitanimmittance and logoaudiometry); evaluation of Central Auditory Processing (CAP); audio recordings of speech samples pre and post ACHT. The speech samples were digitized, edited, and analyzed, using TextGrid files generated in the segmentation and labeling of the files in the Praat software. The labeling was performed manually according to the script from the Script ProsodyDescriptorExtractor, which extracted a set of prosodic acoustic parameters from the duration domains (speech rate, articulation rate, IPI and duration of silent and filled breaks and from the VV units), frequency (median f0, minimum f0, maximum f0, the average of the first derivative f0), intensity (LTAS decline and spectral emphasis) and vocal quality indicators (spectral emphasis, LTAS decline, HNR and SPI). The perceptual and acoustic data were integrated in a qualitative approach, observing the correspondence of the set of perceptual findings to the descriptive statistics of the explored acoustic measures. RESULTS: Subject 1 a presented an increase in f0 variability and in speech rate with better demarcation of the accent groups. The subjects 2 and 3 showed an increase in the rate of utterance and a decrease in silent pauses, being the last with a broader evolution in terms of CAP skills. And Subject 4 showed an increase in speech rate with a slight increase in the interval between silent pauses and improvement in parameters related to vocal quality. CONCLUSION: In addition to the particularities detected, the group of subjects studied revealed, in the post- ACHT period, an evolution in terms of the auditory skills of ordering and naming temporal patterns, a deep auditory figure and dichotic listening. From the point of view of speech production, such clinical evolution was concentrated on acoustic indicators of the spheres of duration (duration of VV units, speech rate, duration of breaks and inter-break interval (IPI)), frequency variability and vocal quality (spectral decline (LTAS), Smooth Phonation Index (SPI), Harmonic-to-Noise Ratio (HNR) and Spectral Emphasis (emph), which found correspondence to perceptual elements of continuity and pitch, in addition to vocal quality adjustments, especially from the supralaryngeal and tension spheres